2023
DOI: 10.3389/fpubh.2022.1017105
|View full text |Cite
|
Sign up to set email alerts
|

Associations between air pollutant and pneumonia and asthma requiring hospitalization among children aged under 5 years in Ningbo, 2015–2017

Abstract: IntroductionExposure to ambient air pollutants is associated with an increased incidence of respiratory diseases such as pneumonia and asthma, especially in younger children. We investigated the relationship between rates of hospitalization of children aged under 5 years for pneumonia and asthma and the concentration of air pollutants in Ningbo between January 1, 2015 and August 29, 2017.MethodsData were obtained from the Ningbo Air Quality Data Real-time Publishing System and the big data platform of the Ning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 99 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…A Brazilian study found a 7% relative risk of pneumonia hospitalization for NO 2 at lag1 [ 41 ]. A study conducted in eastern China similarly found that for each 10-unit increase in SO 2 and NO 2 , pediatric pneumonia hospitalizations increased by 11.21% (95% CI:4.70%, 18.10%) and 5.42% (95% CI:3.07%, 7.82%), respectively [ 35 ]. SO 2 is mainly originated from the combustion of coal, oil and other sulfur-containing minerals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Brazilian study found a 7% relative risk of pneumonia hospitalization for NO 2 at lag1 [ 41 ]. A study conducted in eastern China similarly found that for each 10-unit increase in SO 2 and NO 2 , pediatric pneumonia hospitalizations increased by 11.21% (95% CI:4.70%, 18.10%) and 5.42% (95% CI:3.07%, 7.82%), respectively [ 35 ]. SO 2 is mainly originated from the combustion of coal, oil and other sulfur-containing minerals.…”
Section: Discussionmentioning
confidence: 99%
“…During our study period, the average daily NO 2 concentration in Lanzhou was 48.2 µg/m 3 . In comparison, the average NO 2 concentrations in Ningbo and Guangzhou, China were 39.7 µg/m 3 and 45.2 µg/m 3 [ 17 , 35 ]. Gender differences in the effects of air pollution on respiratory disease in children still exist and the corresponding mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, studies have consistently reported that both short- and long-term exposures to particulate matter were associated with decreases in lung function parameters in children and adolescents [ 117 ]. High levels of air pollution have also been linked to an increased risk of asthma, pneumonia and other respiratory conditions [ 118 ]. Tobacco smoke is a major source of indoor air pollutants.…”
Section: The Chinese Situationmentioning
confidence: 99%
“…The latest research results have found a significant correlation between PM2.5 and hospitalization rates for pneumonia and asthma in children under five years old. For every 10-unit increase in lag03 air pollutant concentration, hospitalization of children with pneumonia and asthma increased by 2.22% [ 16 ]. In addition, PM2.5 is susceptible to including toxic and harmful substances (e.g., heavy metals, microorganisms, etc.…”
Section: Introductionmentioning
confidence: 99%